Biochemical and molecular identification with antimicrobial susceptibility of bacterial species isolated from organs and tissues of Alectoris chukar subspecies Kurdistanica - Rahman, Heshu Sulaiman; Ali, Kwestan Najm; Abdulrahman, Nawzad Rashid; Rashid, Peshnyar Muhammad Atta; Mahmood, Alan Ahmed; Othman, Hemn Hassan; Amin, Kawa; Abdullah, Rasedee (Sulaimani Journal for Pure and Applied Sciences, 2020)
The current study was conducted on 50 Alectoris chukar subspecies Kurdestanica that was collected from Sulaymaniyah Province, Kurdistan Region, Northern Iraq, during the period of April to the end of September 2016. Samples of liver, gallbladder, spleen, kidneys, heart, lungs, gizzard, breast, and thigh muscle tissues were tested for bacterial isolates. Preliminary characterization of the isolated bacteria was carried out by morphological and biochemical methods. The VITEK 2® system was used to confirm the isolated species, while the polymerase chain reaction (PCR) was used for the detection of the resistance gene in the bacterial isolates. As a result, tested samples showed the presence of Staphylococcus sciuri and Escherichia coli. Additionally, antimicrobial susceptibility test was done to determine the bacterial susceptibility to various antibiotics and as a result; E. coli showed 100% susceptibility to penicillin, azithromycin, tetracycline, and doxycycline and 75% susceptibility to streptomycin. On the other hand, S. sciuri exhibited 75% susceptibility to azithromycin, penicillin, and doxycycline, 50% susceptibility to streptomycin, and 25% susceptibility to tetracycline. Molecular identification showed that only the S. sciuri isolates carried the methicillin-resistant mecA gene. To our knowledge, this is the first record of isolationof the S. sciuri methicillin-resistant mecA gene from A. chukar subspecies Kurdestanica.
Keywords: Bacterial isolates; wild bird; biochemical test; VITEK 2 system; antibiotic susceptibility; gene sequencing